5
$\begingroup$

Is there another differentiable monotone increasing (or decreasing) function $ f:\mathbb{R} \rightarrow \mathbb{R} $ with a property that $ f(xy) = f(x) + f(y) $, like the log-function has it?

$\endgroup$
7
  • 1
    $\begingroup$ Trivially $f(x) = 0$, $\forall x \in \mathbb{R}$ has this property. $\endgroup$ Aug 25 '15 at 9:27
  • $\begingroup$ Well, sorry, I didn't mean some trivial functions. I'll edit my question. $\endgroup$
    – DDCh
    Aug 25 '15 at 9:28
  • 4
    $\begingroup$ mathoverflow.net/questions/22706/… $\endgroup$ Aug 25 '15 at 9:29
  • 2
    $\begingroup$ For positive $x$, $f(x) = c \log_e (x)$ is the general solution which includes the zero function and logarithms to other bases. $\endgroup$
    – Henry
    Aug 25 '15 at 9:30
  • 2
    $\begingroup$ There is no such nontrivial function, including the $\log$. Such a function cannot be well defined at $0$, since $f(0\cdot x)=f(0) + f(x)$ for all $x$, meaning that $f=0$. $\endgroup$
    – 5xum
    Aug 25 '15 at 9:38
2
$\begingroup$

Here is the standard derivation of the solution to the functional equation in question:

Suppose $f:(0,\infty)\to\mathbb R$ satisfies $f(xy)=f(x)+f(y)$ for all $x,y\in(0,\infty)$ and $f$ is monotone.

Now, define $g:\mathbb R\to\mathbb R$ and $g(x)=f(\exp(x))$. $g$ satisfies $g(x+y)=f(\exp(x+y))=f(\exp(x)\cdot\exp(y))=f(\exp(x))+f(\exp(y))=g(x)+g(y)$ and $g$ is monotone too.

Let $P(x,y)$ be the assertion $g(x+y)=g(x)+g(y)$. From this we can deduce: $$ P(x,0): g(x)=g(x)+g(0)\iff g(0)=0 \\ P(x,-x): g(0)=g(x)+g(-x)\iff g(-x)=-g(x) $$ Furthermore, we can prove inductively $g(x_1+x_2+…+x_n)=g(x_1)+g(x_2)+…+g(x_n)$ and therefore: $$ g(nx)=g(\underbrace{x+x+…+x}_{n})=\underbrace{g(x)+g(x)+…+g(x)}_{n}=n\cdot g(x) $$ and $$ g(x)=g\left(n\cdot\frac{x}{n}\right)=n\cdot g\left(\frac{x}{n}\right) \iff g\left(\frac{x}{n}\right)=\frac{g(x)}{n} $$ for $n\in\mathbb N$.

Consequently, we have $g\left(\frac{p}{q}\right)=p\cdot g\left(\frac{1}{q}\right)=\frac{p}{q}\cdot g(1)$ for $p,q\in\mathbb N$ and thus $g(r)=r\cdot g(1)$ for all $r\in\mathbb{Q_+}$. Together with $g(-x)=-g(x)$ we can deduce that $g(r)=r\cdot g(1)$ for all $r\in\mathbb{Q}$.

Now suppose $g$ is monotone increasing and there exists a $x\in\mathbb{R}$ for which $g(x)>x\cdot g(1)$. Because the rationals are dense, we can choose an $r\in\mathbb{Q}$ with $g(x)>g(r)=r\cdot g(1)>x\cdot g(1)$. This implies $x≥r$ and $r>x$, contradiction (note that $g(1)$ has to be positive).

The same idea works if $g(x)<x\cdot g(1)$ and also if $f$ is monotone decreasing.

So we conclude that $g(x)=c\cdot x$ for a fixed $c\in\mathbb R$ and for all $x\in\mathbb R$.

This implies $f(\exp(x))=c\cdot x \iff f(x)=c\cdot\ln(x)$. Here, we have either $c=0$ or $c=\log_a(e)$ for some $a\in\mathbb{R_{>0}}$ so either $f(x)=0$ or $f(x)=\log_a(x)$ for all $x\in(0,\infty)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.